Time to reconsider foot and leg position during the bench press - Nuzzo, J. L. (Strength and Conditioning Journal, 2021)
The "feet on the floor" guideline for the bench press is a historical byproduct of old bench designs. The "psoas-relaxed position," where the hips and knees are flexed and the feet rest on adjustable plates at the end of the bench, should be considered to replace existing guidelines. The psoas-relaxed position accommodates lifters of all body heights, is more sport-specific than current bench press posture, and reduces lumbar lordosis and increases the cross-sectional area of the dural sac and spinal canal, making the exercise more viable for certain back pain patients. Steps to implementation include research on bench press postural preferences, development of adjustable foot plates, and formal revision to bench press guidelines.